2016
DOI: 10.1080/13880209.2016.1266673
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidant, anti-inflammatory and anti-septic potential of phenolic acids and flavonoid fractions isolated from Lolium multiflorum

Abstract: Context: Interest has recently renewed in using Lolium multiflorum Lam. (Poaceae) (called Italian ryegrass; IRG) silage as an antioxidant and anti-inflammatory diet.Objective: This study investigated the antioxidant, anti-inflammatory and anti-septic potential of IRG silage and identified the primary components in IRG active fractions.Materials and methods: Total 16 fractions were separated from the chloroform-soluble extract of IRG aerial part using Sephadex LH-20 column before HPLC analysis. Antioxidant and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
24
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(24 citation statements)
references
References 47 publications
0
24
0
Order By: Relevance
“…In this study, the inflammatory responses were significantly suppressed by date seeds at all doses tested (p < 0.05), as depicted in the differences in enzyme activities between the treatment groups and the negative control group. The anti-inflammatory effects of the seeds may be associated with polyphenolic compounds and flavonoids, as shown in their ability to inhibit the production of nitric oxide (NO), TNF-α, and IL-6 [17].…”
Section: Discussionmentioning
confidence: 99%
“…In this study, the inflammatory responses were significantly suppressed by date seeds at all doses tested (p < 0.05), as depicted in the differences in enzyme activities between the treatment groups and the negative control group. The anti-inflammatory effects of the seeds may be associated with polyphenolic compounds and flavonoids, as shown in their ability to inhibit the production of nitric oxide (NO), TNF-α, and IL-6 [17].…”
Section: Discussionmentioning
confidence: 99%
“…These antioxidant compounds are able to scavenge a wide range of reactive species and are capable of inhibiting the expression of genes that are important for the production of inflammatory mediators such as nitric oxide (NO) (Tuñón et al, 2009;Costa et al, 2012). Moreover, studies with different plantbased extracts showed that the presence of phenolic compounds, flavonoids and gallic acid inhibits the production of inflammatory cytokines such as tumour necrosis factor alpha (TNF-α), an important mediator involved in systemic inflammation, acute phase reaction and the production of other cytokines and mediators (Choi et al, 2017;Yoo et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Myricetin (3,3′,4′,5,5′, is an abundant flavonoid compound extracted from natural ingredients such as berries, herbs and vegetables (Salvamani et al, 2014). It contributes to the prevention and/or delay of various pathological processes including cancer, neurodegenerative diseases, and inflammatory disorders (Choi et al, 2017;Domitrovic et al, 2015). However, little is concerned about its preventive response on LPS-induced lung injury.…”
Section: Introductionmentioning
confidence: 99%